2021
DOI: 10.1007/s00431-021-04218-5
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory monitoring of red blood cell transfusions in preterm infants

Abstract: Clinical improvement after red blood cell (RBC) transfusions in preterm infants remains debated. This study aims to investigate the effect of RBC transfusion on the occurrence of desaturations and hypoxia, and other cardiorespiratory outcomes in preterm infants. In this longitudinal observational study, prospectively stored cardiorespiratory parameters of preterm infants who received at least one RBC transfusion between July 2016 and June 2017 were retrospectively analyzed. Sixty infants with 112 RBC transfusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…This might be explained by improved tissue oxygenation in central nervous system. There are studies with and without improvement of apnea of prematurity by ET (6,14). We found that HR and RR were not different throughout 72 hours before and after ET.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…This might be explained by improved tissue oxygenation in central nervous system. There are studies with and without improvement of apnea of prematurity by ET (6,14). We found that HR and RR were not different throughout 72 hours before and after ET.…”
Section: Resultsmentioning
confidence: 52%
“…Kasat et al (31) noticed that tachycardia was the most sensitive predictor of anemia and ET improved apnea, bradycardia, desaturation, tachycardia and oxygen requirements. In this study, indication for ET was only anemia, determined by routine (2,14,30). Studies stated the less BW and GA, the higher need of ET (28).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Improved ways to display physiological data trends may stimulate the clinician’s responsiveness in adding or weaning interventions based on the patient’s changing condition [ 20 ]. We already showed that physiological data can reflect the cardiorespiratory effect of red blood cell transfusions and the respiratory effect of doxapram that is used to treat apnea of prematurity, although the clinical impact of these findings need to be further investigated prospectively [ 10 , 21 ]. Vinks et al developed a model-informed and individualized pharmacokinetic profile aiming for enhanced individualized and evidence-based pharmacotherapy, resulting in better clinical efficacy and safety with fewer side effects [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…High-volume or high-rate transfusions may increase the risk of transfusion associated circulatory overload (TACO), a leading cause of transfusion-associated morbidity and mortality in adults 39. Neonatal TACO is poorly defined and the true incidence of this and other transfusion-related lung injuries in neonates is not known; observational studies have shown variable outcomes 37 40–42. However, it should be noted that weight-related volumes transfused to non-bleeding neonates (usually 10–20 mL/kg) are commonly higher than those for adults (typically, 350 mL for packed red cells and 200–300 mL for platelets, which equates to <5 mL/kg for an 80 kg adult) 27 43 44.…”
Section: Discussionmentioning
confidence: 99%